THE INFLUENCE OF RHYTHMIC GYMNASTICS TO PHYSICAL FITNESS LEVEL IN STATE VOCATIONAL SCHOOL - Adam, Geo; Resita, Citra (Universitas Muhammadiyah Mataram, 2019)
The problem in this study is the low level of physical fitness of class X students of SMK Negeri 1 Cikampek. This research aims to know the influence of rhythm gymnastics activity against physical fitness level. This research uses experimental methods with quantitative approach. The population in this research totalled 622 students. Sample research amounted to 29 students with engineering cluster random sampling. The collection of data on research uses of physical fitness test Indonesia. The data were analyzed using t-test with the results of the calculation of t-count of 7.07 compared to t-table 2.16. The results showed that there is the influence of rhythm gymnastics activity against physical fitness level.